BUILDING THE FOUNDATION OF RELIGIOUS TOLERANCE AND COUNTERING RADICALISM IDEOLOGY IN INDONESIA - Alfian Qodri Azizi; Muhammad Faiq; Thiyas Tono Taufiq (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
Human rights enforcement, especially in the aspect of religious freedom in Indonesia, is still unsolved. Violence involving conflicts among religious followers still occurs. It shows that the space for religious freedom is still a critical problem in this country. Indonesia is a multi-cultural country, but a narrow understanding makes plurality the root of hatred and anger. Indeed, diversity will contribute to national development, but on the other hand, it can also trigger horizontal conflicts. This article will unravel the problems that cause religious intolerance and how to overcome the mushrooming of radicalism. This article is qualitative-based research. The data were collected from the library study. The acts of violence caused by wrong religious understanding were analyzed from the Human Rights enforcement, Islamic theology, and socio-juridical viewpoints so that alternative solutions for acts of violence occurring in society, especially among Muslims, can be settled. This study finds that tolerance has its foundations in both religion and positive law in Indonesia. Therefore, any intolerance has no basis, and it will only worsen the image of Islam and make people unsympathetic to religion.